2022
DOI: 10.1039/d2qo01437h
|View full text |Cite
|
Sign up to set email alerts
|

Clerodane diterpenoids with anti-inflammatory and synergistic antibacterial activities from Tinospora crispa

Abstract: Ten new and four known clerodane diterpenoids were isolated from the vine and leaves of Tinospora crispa. The chemical structures and absolute stereochemical configurations of all the compounds were established...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The instruments, materials and reagents used in this study were consistent with those reported in the literature [13,20].…”
Section: General Experimental Proceduressupporting
confidence: 54%
“…The instruments, materials and reagents used in this study were consistent with those reported in the literature [13,20].…”
Section: General Experimental Proceduressupporting
confidence: 54%
“…Therefore, NO inhibitors were considered a promising direction for anti-inflammatory drug research [ 39 ]. Recently, several diterpenes with decalin skeleton have been reported to have significant NO inhibitory activity [ 40 , 41 , 42 ]. Among diterpenes, tinopanoid M, a clerodane diterpenoid isolated from Tinospora crispa, exerts good anti-inflammatory effects by reducing the expression of various pro-inflammatory factors and modulating multiple inflammatory pathways [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…NO Inhibitory Activity and Cytotoxicity on BV-2 Cells. The inhibitory activity of all the isolated compounds on nitric oxide (NO) release was tested by the method described in previous reports 25,26 with minor modifications. In short, 100 μL medium containing 4 × 10 4 BV-2 cells was transferred to each well of the 96-well plate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%